ANALISIS SISTEM DAN PROSEDUR PENGADAAN KEBUTUHAN FARMASI PADA RSUD SULTAN SYARIF MOHAMAD ALKADRIE PONTIANAK - Tan, Elizabeth (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2017)
This research aimed to gauge effectiveness of the procurement system and procedures which implemented by Sultan Syarif Mohamad Alkadrie Pontianak Hospital. The applied research method was qualitative method with descriptive research form. Then, the data analysis technic was conducted with Internal Control Questionaires (ICQ) analysis, flowchartand Organizational Structure. The research outcome showed that Sultan Syarif Mohamad Alkadrie Pontianak Hospital entire system and pharmaceutical need procurement procedures were quite effective and implemented well. This could be traced back from Internal Control Questionaires (ICQ) results that indicated 76,77% for answers â€œYesâ€ and 22,26% untuk answers â€œNoâ€. Based on previous analysis, strictly functional responsibility separation was not implemented which caused employee double function. This research showed there were weaknesses in the procurement planning system causing accumulation of medicine in the warehouse. Implementation of online purchasing system (Epurchasing) caused the incomplete document used in procurement procedures due to perceived government institution perception about effectiveness of the system and procedures.Â Keywords : systems and procedures, analysis, internal control questionnaires